The International Turn in American Studies - Messmer, Marietta; Frank, Armin Paul (Interamericana, 2015)
The volume is a contribution to the ongoing debate on the internationalization of American Studies. The essays by European, American and Latin American scholars provide critical evaluations of a wide range of concepts, including trans-national and post-national, international, trans-atlantic, trans-pacific, as well as hemispheric, inter-American and comparative American studies. Combining theoretical reflections and actual case studies, the collection proposes a reassessment of current developments at a time when American nations experience the paradoxical simultaneity of both weakened and strengthened national borders alongside multiple challenges to national sovereignty.